2008
DOI: 10.2746/095777308x332240
|View full text |Cite
|
Sign up to set email alerts
|

A singular case of traumatic total hoof capsule avulsion

Abstract: Summary Total, full thickness hoof wall avulsion is rare in horses. Sometimes complications such as fracture of the distal phalanx, osteomyelitis, septic arthritis and degenerative joint disease have been reported. Limiting motion at the affected site and hoof stabilisation are essential to obtain a good hoof regeneration. This case report reviews the clinical features including diagnostic techniques (radiographic examination and venography) of a Quarter Horse filly presented with a complete and full‐thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
0
12
1
Order By: Relevance
“…Complete regrowth of the new horn capsule may take up to 9 months (Jackson ; Stanek and Brkic ; de Gresti et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Complete regrowth of the new horn capsule may take up to 9 months (Jackson ; Stanek and Brkic ; de Gresti et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Euthanasia was elected in all the cases herein. However, it is possible to treat cases of hoof slough, but the final outcome, following prolonged costly treatment and time investment, is a deformed hoof (de Gresti et al 2008). The horn of the wall grows from the stratum germinativum of the coronary corium at an average rate of 6-10 mm per month Reilly et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hoof growth rates in mature horses have been reported without stating hoof wall renewal time (Faramarzi et al, 2009;Reilly et al, 1998). In a case of total hoof wall avulsion of a four year old Quarter Horse, it was reported that 24 months after the trauma the hoof had completely regrown implying that this was the length of time for hoof renewal in this case (de Gresti et al, 2008). A number of authors have speculated that the hoof wall grows faster in young horses but only two have measured hoof growth rates in foals (Smallwood et al, 1986;Butler and Hintz, 1977).…”
mentioning
confidence: 99%